Residual effects of frequently available organic amendments on cadmium bioavailability and accumulation in wheat. (April 2020) - Rehman, Muhammad Zia ur; Zafar, Mehwish; Waris, Aisha A.; Rizwan, Muhammad; Ali, Shafaqat; Sabir, Muhammad; Usman, Muhammad; Ayub, Muhammad Ashar; Ahmad, Zahoor
Abstract: Wheat ( Triticum aestivum L.) cultivation in cadmium (Cd) polluted soil is a core concern to food quality and food security all over the world. Cadmium toxicity is mainly associated with a Cd influx from contaminated soils to human via grain consumption. Organic amendments are widely used for Cd immobilization and enhancement in plant growth, but the residual effects of these amendments are mostly unknown. The present study addressed the long-term effects of organic amendments in contaminated soils by evaluating their residual effects on 3rd crop (wheat) in the sequence. Initially six organic amendments viz. rice husk biochar (RHB), wheat-straw biochar (WSB), cotton-stick biochar (CSB), poultry manure (PM), press mud (PrMd) and farm manure (FM) were applied once at a rate of 2% in Cd (50 mg kg −1 ) contaminated soil with wheat-rice rotation. After the harvest of wheat and rice crops, wheat (Var. Galaxy) was again grown in the same pots. Results revealed that plants grown under Cd stress (without any amendment) contain more tissue (root, shoot and grain) and soil AB-DTPA extractable Cd. The soil amended with RHB has shown lowest AB-DTPA extractable Cd (69% lower than control). Similarly, RHB application has significantly reduced wheat root, shoot and grain Cd concentrations compared to control and other amendments. Results have confirmed the effectiveness of RHB residual contents as an active amendment for restriction of Cd in non-bioavailable pool of soil and better growth and yield of wheat. Highlights: Residual effects of rice husk biochar (RHB) and press mud (PrMd) were higher compared to other amendments. The increase in wheat growth and yield was highest in residual RHB treatment. Cd immobilization index was highest in RHB treatment. The grain Cd was below threshold level in RHB treatment.